Analisis Pengelolaan Tanah Wakaf di Wilayah PD Persis Karawang Studi dalam Perspektif Maqashid Syariah - Arif Rahman Hakim; Jafril Khalil (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The waqf assets owned by Karawang Regency are many and very extensive, but many do not understand how to manage waqf land so that it can be useful and its management is in accordance with Islamic sharia. This study aims to examine the management of waqf in the Karawang Regional Leadership of the Islamic Association (Persis). The results of waqf management are analyzed using the Maqashid Syariah principle. This type of research is field research. The data collection techniques used are observation, interviews and documentation. The interview used informants from the Bidgar Perwakafan PD Persis, the Bidgar Perwakafan PC Persis, Nazir, and community leaders. The research approach uses descriptive qualitative and socio history and maqashid sharia approach. This analysis technique uses data reduction, data presentation, and conclusion drawing. The results showed that waqf land in the area of the Regional Leadership of the Islamic Association (Persis) Karawang is managed and intended for mosques, schools, taklim assemblies, and productive rice fields. The management of waqf land carried out by the Karawang Islamic Unity (Persis) PD Waqf Field is not fully in accordance with the principles of maqashid sharia, especially on the principle of hifzh al-Mal.